2019
DOI: 10.1186/s13244-019-0723-9
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal post mortem ultrasound (PMUS): a practical approach

Abstract: Declining rates of consent for standard perinatal autopsy has led to a rise in interest for postmortem imaging as an alternative, non-invasive method for investigation of childhood and perinatal deaths. Whilst much interest has focussed on cross-sectional techniques such as postmortem CT (PMCT) or MRI (PMMR), other modalities including postmortem ultrasound (PMUS) have been shown to have reasonable diagnostic accuracy rates, with the added benefit of being more readily accessible and affordable. There is littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…They were blinded to all other clinical history details (including results of antenatal imaging tests). PMUS was conducted according to published guidelines, and each study took approximately 20 minutes to complete. All bodies were stored and refrigerated at 4°C in the hospital mortuary prior to imaging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were blinded to all other clinical history details (including results of antenatal imaging tests). PMUS was conducted according to published guidelines, and each study took approximately 20 minutes to complete. All bodies were stored and refrigerated at 4°C in the hospital mortuary prior to imaging.…”
Section: Methodsmentioning
confidence: 99%
“…One recent study even suggested that fetal and neonatal PMUS could provide the same diagnostic accuracy for cause of death as 3T PMMR, when the images were of diagnostic quality . With ultrasound imaging being more affordable and less time‐consuming (approximately 20 min for PMUS versus 45‐90 min for PMMR), one potential imaging protocol may be to use PMUS as a triage tool for non‐invasive autopsies (NIAs), whilst referring only complex cases or nondiagnostic PMUS studies for PMMR, thus saving time and clinical resources. This pathway could be streamlined further if it was possible to predict certain variables or patient factors that would render a nondiagnostic quality PMUS and “fast‐track” these cases for PMMR.…”
Section: Introductionmentioning
confidence: 99%
“…Although not currently routinely performed in many centres, post‐mortem ultrasound (PMUS) has been shown to be a feasible technique for post‐mortem imaging with good concordance rates compared with autopsy of up to 81.4% [73.2%‐89.6% CI] (Figure ). The techniques described in the literature commonly utilise high frequency linear probes for the majority of body parts (eg, frequencies of 6‐18 or 6‐12 MHz for GE Voluson E8 model; 7‐16 MHz for Samsung HM70A model; 10‐15 MHz for Toshiba Aplio 500 model).…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding post‐mortem 1.5T MRI brain imaging in C and D demonstrate how key features of brain sulcation and ventricular appearances can already be well seen on the ultrasound and where diagnostic, further cross‐sectional imaging is not always necessary. Source: Reproduced with permission from Shelmerdine et al, Insights Imaging 2019…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article published within this journal [9], we described a practical approach to conducting a comprehensive post-mortem ultrasound (PMUS) examination. This covered the basic principles behind foetal preparation for imaging, parental consent, helpful techniques for obtaining optimal PMUS images and the expected normal post-mortem changes.…”
Section: Introductionmentioning
confidence: 99%